UPAYA MENINGKATKAN KINERJA GURU kelas III, IV, dan VI, IV, DAN V DALAM PEMBELAJARAN MELALUI SUPERVISI EDUKATIF KOLABORATIF SECARA PERIODIK DI SD NEGERI 7 SUMERTA - Ni Nyoman Satri (GUNA WIDYA: JURNAL PENDIDIKAN HINDU, 2019)
A teacher must have adequate knowledge in both academic and pedagogical fields. This study is a School Action Research which aims to describe the role of periodic collaborative educative supervision on the performance of teachers in class III, IV, and V, starting from arranging learning plans, implementing learning, assessing learning achievement to giving action go on. The research design chosen was using a cycle model that was carried out repeatedly and continuously (spiral cycle). The cycle model is planned through two cycles in which each cycle includes the stages of plan, action, observation, and reflection. The subject of this school action research was determined using purposive sampling technique, namely teachers who taught in class III, IV, and V SD which amounted to 3 (three) people. Data collection techniques carried out in this study were observation and documentation. The hypothesis was analyzed using qualitative descriptive methods. Data analysis in qualitative research is carried out when data collection takes place, and after completion of data collection for a certain period. The results of school action research found that collaborative educative supervision periodically has a very important role in improving teacher performance in learning in grades III, IV, and V which is indicated by the average value of teacher performance in cycle 1 which is 81.3% and the average teacher performance score in cycle 2 is 85.5%. The average increase that occurs from cycle 1 to cycle 2 is 4.22%.